2022
DOI: 10.3389/fimmu.2022.1060695
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dynamic changes in the peripheral CD8+ T cells function and differentiation in ESCC patients treated with radiotherapy combined with anti-PD-1 antibody or concurrent chemoradiotherapy

Abstract: ObjectiveThe systematic immune status of cancer patients undergoing immunotherapy is little known. We prospectively identified the function and differentiation traits of peripheral CD8+ T cells based on our phase 1b clinical trial (NCT03222440) of radiotherapy combined with camrelizumab in patients with locally advanced esophageal squamous cell carcinoma (ESCC) and compared it with concurrent chemoradiotherapy (CCRT).Methods19 and 18 patients were included in the cohort of radiotherapy plus camrelizumab and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…We also found higher percentages of CD8+ TEMRA cells in the patient cohort with metastatic disease, suggesting that these may have a restricted capacity for performing antitumor cytotoxic activity. In line with this, in a recent report, it was found that in patients with advanced esophageal squamous cell carcinoma receiving radiotherapy combined with immunotherapy, PD-1+ CD8+ T lymphocytes exhibited higher functional and activated characteristics and had enhanced memory properties (including both EM and CM subsets) and less TEMRA cells than PD-1-CD8+ T lymphocytes [25]. Our study also revealed similar CD8+ T subset profiles for our PCa patient cohorts stratified by tumor aggressiveness.…”
Section: Discussionsupporting
confidence: 90%
“…We also found higher percentages of CD8+ TEMRA cells in the patient cohort with metastatic disease, suggesting that these may have a restricted capacity for performing antitumor cytotoxic activity. In line with this, in a recent report, it was found that in patients with advanced esophageal squamous cell carcinoma receiving radiotherapy combined with immunotherapy, PD-1+ CD8+ T lymphocytes exhibited higher functional and activated characteristics and had enhanced memory properties (including both EM and CM subsets) and less TEMRA cells than PD-1-CD8+ T lymphocytes [25]. Our study also revealed similar CD8+ T subset profiles for our PCa patient cohorts stratified by tumor aggressiveness.…”
Section: Discussionsupporting
confidence: 90%
“…[48] EC has increased expression levels of HLA-DR after immunotherapy. [49] Limited studies Lymphocyte%leukocyte in tumors have shown phocytes to be an indicator of good overall survival in a study that combined peripheral blood inflammation indices to predict survival in patients with small cell lung cancer. [50] B cells are an important subset of lymphocytes involved in humoral immunity within the adaptive immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, numerous studies have indicated that immune cell phenotypes can serve as central biomarkers for immunotherapy. [ 49 , 59 , 68 70 ] Therefore, the 15 negative immune phenotypes we analyzed in our research may be essential biomarkers supporting immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…At the advanced unresectable ESCC stage, Wei et al [ 99 ] conducted a phase Ib clinical trial of first-line treatment with RT combined with the anti-PD-1 antibody camrelizumab in patients with locally advanced ESCC who were CCRT intolerant or refused CCRT, versus ESCC patients with CCRT alone for dynamic changes in peripheral blood CD8 T-cell function and differentiation comparison. The results showed that in the RT combined with camrelizumab group, camrelizumab effectively bound to PD-1 on CD8 T cells and competed directly with PD-L1 on tumor cells, thereby reducing the suppressive effect of tumor cells on immune cells.…”
Section: Reversal Strategy Of Escc Radioresistancementioning
confidence: 99%
“…The results showed that in the RT combined with camrelizumab group, camrelizumab effectively bound to PD-1 on CD8 T cells and competed directly with PD-L1 on tumor cells, thereby reducing the suppressive effect of tumor cells on immune cells. Tcm subsets and Tem subsets were increased in PD-1CD8 T cells after RT plus camrelizumab treatment, whereas only Tcm subsets were increased after CCRT treatment, suggesting that RT with camrelizumab treatment may exhibit a stronger CD8 T-cell response than CCRT [ 99 ]. Based on the stronger T-cell immune response with RT in combination with camrelizumab than with CCRT, Zhang et al [ 100 ] further explored the safety and feasibility of combining CCRT with camrelizumab as a first-line treatment for patients with locally advanced ESCC.…”
Section: Reversal Strategy Of Escc Radioresistancementioning
confidence: 99%